2019
DOI: 10.1021/acs.chemmater.8b04436
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Right Bricks for Molecular Legos: A Data Mining Approach to Organic Semiconductor Design

Abstract: Improving charge carrier mobilities in organic semiconductors is a challenging task that has hitherto primarily been tackled by empirical structural tuning of promising core compounds. Knowledge-based methods can greatly accelerate such local exploration, while a systematic analysis of large chemical databases can point towards promising design strategies. Here, we demonstrate such data mining by clustering an inhouse database of > 64.000 organic molecular crystals for which two charge-transport descriptors, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 104 publications
0
63
0
Order By: Relevance
“…[48] Schober et al have screened the CSD for monomolecular organic crystals with the objective to identify organic semiconductors with high charge carrier mobility. [31,57,58] For this study, we extracted molecules from the crystals and relaxed them in vacuum with the aforementioned computational parameters. The OE dataset is not yet publicly available.…”
Section: Ii2 Aa: 44 K Amino Acids and Dipeptidesmentioning
confidence: 99%
“…[48] Schober et al have screened the CSD for monomolecular organic crystals with the objective to identify organic semiconductors with high charge carrier mobility. [31,57,58] For this study, we extracted molecules from the crystals and relaxed them in vacuum with the aforementioned computational parameters. The OE dataset is not yet publicly available.…”
Section: Ii2 Aa: 44 K Amino Acids and Dipeptidesmentioning
confidence: 99%
“…[33][34][35] Our study indicated that this machine-learning strategies may provide OFET researchers supporting details to fine-tune the electronic structure and thus the charge transport property of the n-type organic materials. [33][34][35] Our study indicated that this machine-learning strategies may provide OFET researchers supporting details to fine-tune the electronic structure and thus the charge transport property of the n-type organic materials.…”
mentioning
confidence: 76%
“…This is particularly relevant in a high-throughput setting, e. g. when a large chemical reaction network with many intermediates and transition states is to be explored, or a large chemical space is of interest. [10][11][12][13] The wide range of ML methods that have emerged in this context raises the question which one should be used for a given application. Since the atomization energy (AE) has a long tradition as the foremost benchmark property to judge the accuracy of quantum chemical approximations, [14][15][16] it has also become one of the standard targets to illustrate the accuracy of novel ML methods.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the performance of the models is compared across different size-ranges both within the QM9 database and between databases going up to molecules with more than 80 heavy atoms. [11,22]…”
Section: Introductionmentioning
confidence: 99%